PENGARUH CAFE ATMOSPHERE DAN FOOD QUALITY TERHADAP REVISIT INTENTION DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL MEDIASI DI KOPI JANJI JIWA INDONESIA - Hazlirahman, Fajar; Kalis, Maria Christiana Iman; Purmono, Bintoro Bagus; Afifah, Nur; Setiawan, Harry (Al-Idarah, 2025)
This study contributes to examining the influence of cafe atmosphere and food quality on revisit intention, with customer satisfaction as a mediating variable at Kopi Janji Jiwa. A quantitative method was employed using purposive sampling, involving 273 respondents. Data were analyzed using SmartPLS 4 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The hypothesis testing revealed that both cafe atmosphere and food quality significantly affect customer satisfaction. Furthermore, food quality and satisfaction directly influence revisit intention. However, cafe atmosphere does not have a direct impact on revisit intention but shows an indirect effect through customer satisfaction. These findings emphasize that food quality and cafe atmosphere play a crucial role in shaping customer satisfaction, which in turn drives revisit intention. Although cafe atmosphere was not found to have a direct effect, its influence becomes significant when customers are satisfied.This study contributes to examining the influence of cafe atmosphere and food quality on revisit intention, with customer satisfaction as a mediating variable at Kopi Janji Jiwa. A quantitative method was employed using purposive sampling, involving 273 respondents. Data were analyzed using SmartPLS 4 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The hypothesis testing revealed that both cafe atmosphere and food quality significantly affect customer satisfaction. Furthermore, food quality and satisfaction directly influence revisit intention. However, cafe atmosphere does not have a direct impact on revisit intention but shows an indirect effect through customer satisfaction. These findings emphasize that food quality and cafe atmosphere play a crucial role in shaping customer satisfaction, which in turn drives revisit intention. Although cafe atmosphere was not found to have a direct effect, its influence becomes significant when customers are satisfied.